High throughput screening of particle conditioning operations: II. Evaluation of scale‐up heuristics with prokaryotically expressed polysaccharide vaccines. Issue 8 (22nd June 2015) - Noyes, Aaron; Huffman, Ben; Berrill, Alex; Merchant, Nick; Godavarti, Ranga; Titchener‐Hooker, Nigel; Coffman, Jonathan; Sunasara, Khurram; Mukhopadhyay, Tarit
ABSTRACT Multivalent polysaccharide conjugate vaccines are typically comprised of several different polysaccharides produced with distinct and complex production processes. Particle conditioning steps, such as precipitation and flocculation, may be used to aid the recovery and purification of such microbial vaccine products. An ultra scale‐down approach to purify vaccine polysaccharides at the micro‐scale would greatly enhance productivity, robustness, and speed the development of novel conjugate vaccines. In part one of this series, we described a modular and high throughput approach to develop particle conditioning processes (HTPC) for biologicals that combines flocculation, solids removal, and streamlined analytics. In this second part of the series, we applied HTPC to industrially relevant feedstreams comprised of capsular polysaccharides (CPS) from several bacterial species. The scalability of HTPC was evaluated between 0.8 mL and 13 L scales, with several different scaling methodologies examined. Clarification, polysaccharide yield, impurity clearance, and product quality achieved with HTPC were reproducible and comparable with larger scales. Particle sizing was the response with greatest sensitivity to differences in processing scale and enabled the identification of useful scaling rules. Scaling with constant impeller tip speed or power per volume in the impeller swept zone offered the most accurate scale up, with evidence that time integration of these values provided the optimal basis for scaling. The capability to develop a process at the micro‐scale combined with evidence‐based scaling metrics provide a significant advance for purification process development of vaccine processes. The USD system offers similar opportunities for HTPC of proteins and other complex biological molecules. Biotechnol. Bioeng. 2015;112: 1568–1582. © 2015 Wiley Periodicals, Inc.